Answer:
see explanation
Explanation:
(a)
4x² - 9 ← is a difference of squares which factors in general as
a² - b² = (a + b)(a - b)
4x² = (2x)² ⇒ a = 2x and 9 = 3² ⇒ b = 3, thus
4x² - 9 = (2x + 3)(2x - 3)
----------------------------------------------
(b)
g - 3m = am + 5 ( collect the terms in m together )
Add 3m to both sides
g = am + 3m + 5 ( subtract 5 from both sides )
g - 5 = am + 3m ← factor out m from each term
g - 5 = m(a + 3) ← divide both sides by (a + 3)
m =
![(g-5)/(a+3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n3lhhs49uhr6z6ld4tj8jh9u06z53lclr8.png)